OVERALL EQUIPMENT EFFECTIVENESS (OEE) THROUGH TOTAL PRODUCTIVE MAINTENANCE (TPM) PRACTICES: A CASE STUDY IN CHEMICAL INDUSTRY - Agung, Ferry Yulius; Siahaan, Antonius (Emerging Markets : Business and Management Studies Journal, 2019)
In present world scenario, when manufacturing companies encounter capacity problems, they immediately look for increasing overtime, number of shifts and purchase new machine and equipment’s. Instead, focus must be on the better utilization of resources and increasing performance of the existing machines, so that there is better equipment performance, reduction in bottlenecks, decrease overall downtime, improve operator performance and minimization of setup time and other major forms of losses thus enabling in decision on the investment of buying new machines. Thus, the aim of this journal is to study the state of Overall Equipment Effectiveness (OEE) through Total Productive Maintenance (TPM) in Chemical Industry. theoretical framework is developed to determine the predominant TPM pillars that influence the OEE. Based on this theoretical framework, a survey methodology is used where questionnaires are sent to 180 respondents in PT.XYZ with the resulting response rate of 100% which is comparable with other studies. Theoutcome of this survey is analyzed using SPSS and the analysis show that the predominant TPM pillars indeed has a considerable impact on the OEE.